The use of geoinformation technologies for the formation of a special passability map - Cherenko, Aliaksei S.; Kurlovich, Dzmitry M. (Journal of the Belarusian State University. Geography and Geology, 2023)
Using software products of the design bureau «Panorama» and the software and information complex «Compilation of special map» developed by the United Institute of Informatics Problems of the National Academy of Sciences of Belarus, the methodology for creating a passability map is described. The initial cartographic materials for their creation are considered and analysed. When studying them, the features in the rules of digital description of vector objects of topographic maps were revealed, which do not allow to create a high-quality passability map, therefore, changes for them were proposed. Instead of dividing the passability map by seasons, a classification based on climatic and weather conditions based on the surface condition of the soil is proposed. A passability map was created for the traditional approach designed to be imprinted into analog topographic maps. To increase its informativeness, new symbols were developed. For the geoinformation approach intended for use on a computer, a passability map was created for sharing with remote sensing data and a graph of roads. It is proposed to involve GIS specialists, engineering troops, intelligence, with knowledge of the tactical and technical characteristics of the weapons used in the development of the passability map. It is concluded that it is necessary to create a topographic basis for the entire the Republic of Belarus and the adjacent territory without dividing by nomenclature sheets, taking into account modern requirements that are imposed on the troops.